64 Gold standards Framework implementation to improve individual plan of care for patients in the last year of life. (14th March 2023) - Bowen, Joanne; Hall, Kate; Hickey, Michele
Abstract : Introduction: A third of hospital patients are in their last year of life and almost 50% of people die in hospital. At Dudley Group NHS Foundation Trust (DGFT) we have implemented the Gold Standards Framework (GSF) to support identification of patients in the last year of life and development of individual plan of care. Method: A GSF document is completed on the hospital electronic patient record following identification and there is one document per admission which is used to record if advance care planning has been offered, commencement of priorities for care and preferred place of care documented. Results: From previous audits completed in the Trust we have confirmed approximately 30% of patients at anyone time are in the last year of life and this can also be reported by ward to support individual wards. The percentage of patients identified as GSF is increasing and as of June 2022 this was 14% and the percentage of GSF red patients with Priorities for care communication document has improved to 49% and the target is 70%. Discussion: A number of initiatives are being used to improve identification of patients in the last year of life including introduction of level 2 priority training and also working with Deteriorating patient group on a bespoke 12 week course to support wards with the timely identification and appropriate management of deteriorating patients.